How to Enrich the Future Science Program. - Dowling, Thomas I. (Education, 1945)
This article focuses on how to enrich the science program of the future. A teacher is an effective one if he or she can enrich the experiences of students. Students, also, have a part to play in the enrichment of a program if they are to gain the greatest value from instruction. The best program of science instruction is to be found where the teacher and the student help each other in sharing experiences. The science program of the future will see a growth in the school science museum. This museum may consist of a corner of classroom which has been set aside as a museum, a place where students assemble exhibits which illustrate the science principles they are studying. A good science library is also essential to an enriched program of teaching, as well as experiment and observation.